1994
DOI: 10.7164/antibiotics.47.1010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of balanol from Verticillium balanoides and ophiocordin from Cordyceps ophioglossoides.

Abstract: Recently, we reported the isolation of the potent protein kinase C inhibitor balanol (1) from the fungus Verticillium balanoides.In an earlier study, Konig et al. reported the isolation of ophiocordin (3), a structural isomer of 1, from the fungus Cordyceps ophioglossoides. The present study was designed to clarify whether or not balanol and ophiocordin are different compounds. The results indicated that the two fungi produced the same compound, the structure being that assigned to balanol. In addition, a thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…IR spectra were recorded on a Perkin-Elmer RXI FT-IR spectrometer. 1 13 C NMR. All spectra were recorded at 25 8C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra were recorded on a Perkin-Elmer RXI FT-IR spectrometer. 1 13 C NMR. All spectra were recorded at 25 8C.…”
Section: Methodsmentioning
confidence: 99%
“…Some PKC inhibitors are currently in clinical trials for various types of cancer. [8][9][10] Balanol (1 a), an unusual metabolite isolated by Kulanthaivel et al [11][12][13] from the fungus Verticillium balanoides collected from Pinus palustris needle litter in 1993, and later by Ohshima et al from Fusarium merismoids in 1994, [12] inhibits almost all PKC isoforms in the 4-5 nanomolar range. Ophiocordin (3), [14,15] a regioisomer of (À)-balanol (1 a), was isolated from Cordyceps ophioglossoides in 1977 and serves as an antibiotic with antifungal activity.…”
Section: Introductionmentioning
confidence: 98%
“…Balanol, an ATP mimetic and one of the most potent natural product protein kinase inhibitors discovered to date, is one such template particularly amenable to analogue design. The isolation of balanol ( Figure 1) may have been reported initially with the name of ophiocordin, an antifungal metabolite produced by Cordyceps ophioglossoides (82)(83)(84). Sixteen years after the initial characterization of ophiocordin, the absolute stereochemical structure of balanol, its isolation from Verticillium balanoides and its low nanomolar inhibitory effects against nearly all protein kinase C (PKC) isoforms were reported (81).…”
mentioning
confidence: 99%
“…Two pure compounds were isolated as active principles from low molecular-weight fractions, and a protein-bound polysaccharide that showed a marked increase in the liver enzyme activities, and a significant inhibition of lipid peroxidation was found. Boros et al (1994) reported that ophiocordin, an anti-fungal antibiotic from Cordyceps ophioglossoides (Kneifel et al, 1977) and balanol from Verticillium balanoides are structurally identical. This may indicate a particularly close taxonomic relationship between the two taxa.…”
Section: Pure Compoundsmentioning
confidence: 99%